Manajemen Quality Control SCTV dalam Menjaga Kualitas Tayangan Sinetron - Anita Sofyanti Dewi, sofy; Pamungkas, Andhika; Mustika, Sri (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2025)
This study aims to explore the management of Quality Control (QC) in television stations, particularly in entertainment programs such as soap operas, to maintain broadcast quality and ensure compliance with applicable regulatory standards. SCTV's soap opera programs are aired during prime time, making the QC division play a strategic role in ensuring that broadcasts meet quality standards and broadcasting regulations, including P3SPS. The research employs Peter K. Pringle's strategic management theory, which includes planning, organizing, implementation, and supervision stages. A qualitative approach with a case study method is used. Data were collected through participatory observation and interviews with the head of the Programming Services division, the head of the QC division, and one QC staff member at SCTV Tower. Data analysis follows the Miles and Huberman model, encompassing data reduction, data presentation, and conclusion drawing. The findings reveal that SCTV's QC division has successfully implemented broadcasting management strategies. The key to success lies in adherence to established SOPs and effective communication between the division head and QC crew. This research provides significant insights into how QC management contributes to maintaining the quality of soap opera broadcasts while complying with broadcasting regulations in the television industry.